Preparation of the Digital Elevation Model using open source Geographic Information Systems tools for 3D prints - Chwiałkowski Cyprian; Zydroń Adam (Polish Cartographical Review)
The presentation of landforms in two-dimensional graphics may not always be clear and understandable to every viewer. The presentation of landforms, as well as other types of characteristics and issues in three-dimensional space can bring many advantages in the process of better understanding of the surrounding reality. The primary purpose of this research is to put forward a simple scheme, accessible to any Geographic Information Systems user, for generating 3D physical terrain models for any area of the Earth. The presented scheme can be used anywhere in the world, however, for the purpose of illustrating its capabilities, a case study of a selected area – the Tatra Mountain range – was conducted in this paper. As part of the study, a 3D model was developed based on a Digital Elevation Model obtained from an open source, i.e. MapTiler. An indisputable advantage of the study is that the designed process flow in its structure takes into account only generally available tools and software (the model was prepared in the QGIS program). However, a certain limitation is the process of printing itself, which depends on the availability of specialized printing equipment. In this case study, FDM (Fused Deposition Modeling) technology was used for printing, and the model itself was prepared on a Creality Ender 7 printer. The proposed flowchart, on the one hand, unifies and simplifies the process of creating physical 3D models, while on the other hand, it provides opportunities for GIS users and developers to develop the proposed solution.